Evaluation of the analytical performance of a portable ion-selective electrode meter for measuring whole-blood, plasma, milk, abomasal-fluid, and urine sodium concentrations in cattle - A. A., Megahed; Hiew, M.; Grünberg, W.; Trefz, F. M.; Constable, P. D. (Elsevier, 2019)
A portable ion-selective electrode (ISE) meter (LAQUAtwin B-722; Horiba Instruments Inc., Irvine, CA) is available for measuring the sodium ion concentration ([Na]) in biological fluids. The objective of this study was to characterize the analytical performance of the ISE meter in measuring [Na] in whole-blood, plasma, milk, abomasal fluid, and urine samples from cattle. Method comparison studies were performed using whole-blood and plasma samples from 106 sick calves and 11 sick cows admitted to a veterinary teaching hospital, 80 milk and 206 urine samples from 16 lactating Holstein-Friesian cows with experimentally induced free water, electrolyte, and acid-base imbalances, and 67 abomasal fluid samples from 7 healthy male Holstein-Friesian calves fed fresh milk with or without an oral electrolyte solution. Deming regression and Bland-Altman plots were used to determine the accuracy of the meter against reference methods. The meter used in direct mode on undiluted samples measured whole-blood [Na] 9.7 mmol/L (7.3%) lower than a direct ISE reference method and plasma [Na] 16.7 mmol/L (12.7%) lower than an indirect ISE reference method. The meter run in direct mode measured milk [Na] 3.1 mmol/L lower and abomasal fluid [Na] 9.0% lower than indirect ISE reference methods. The meter run in indirect mode on diluted samples accurately measured urine [Na] compared with an indirect ISE reference method. We conclude that, after adjustment for the bias determined from Bland-Altman plots, the LAQUAtwin ISE meter provides a clinically useful and low-cost cow-side instrument for measuring [Na] in whole blood, plasma, milk, and abomasal fluid.